EFEKTIFITAS LARUTAN KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) TERHADAP JUMLAH KOLONI BAKTERI DI SALIVA - Sulur Joyo Sukendro; Nono Sulistijarso; Endah Aryati Ekoningtyas; Ratnawati Hendari (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEThe effectiveness of red dragon fruit rind solution (Hylocereus polyrhizus) to bacteria colony in salivaABSTRACTHylocereus polyrhizus or red dragon fruit is a tradisional herb. 30-35% red dragon fruit is a rind often discarded. Rind of dragon fruit is contains natural pigments and antioxidant that are beneficial to dental health. In saliva are many types of bacteria, which can lead to harmful in the mouth Aims to determine the effect of the red dragon fruit peel extract to colonies of bacteria in saliva.Method is true experiment, design is a pre and post test design. Subjects were saliva with a red dragon fruit peel extract concentration of 25%, 50%, 75% and 100% with 3 repetitions. Dragon fruit peel extract obtained by pulverized and then filtered. This type of research is analytic, statistical the Wilcoxon test. Confidence level 95% of p value 0.05. Implementation of research in the Laboratory of Microbiology Dental Health of Nursing Departmens, Politecnique of Health Kemenkes Semarang.Results the effectiveness of the solution concentration red dragon fruit peel extract of colonies bacteria was found at a concentration of 100% (p 0.05), and the lowest concentration of 25% (p 0.05). The active ingredient is a flavonoid. Antifungal and antibacterial effect produced by the red dragon fruit to contain several flavonoids, phenols, Vitamin C, Protein, carbohydrates and antioxidants. This compounds the red dragon fruit is a red and purple on this fruit. Suggestions for further research to be separation of flavonoids contained in the fruit. And for further research on the types of bacteria that effectively eliminated the fruit. Keywords : Rind hylocereus polyrhizus, saliva, bacteria.